2005
DOI: 10.1159/000084996
|View full text |Cite
|
Sign up to set email alerts
|

Increased PGE<sub>2</sub> Levels in Nonmalignant Mucosa Adjacent to Squamous Cell Carcinoma of the Head and Neck

Abstract: Objective: The cyclooxygenases (COX) 1 and 2 are the rate-limiting enzymes of prostaglandin E2 (PGE2) synthesis, and the upregulation of COX-2 has been reported in tumors of different origins. The aim of our study was to quantify the PGE2 expression in squamous cell carcinoma and surrounding mucosa, to analyze the potential of acetylsalicylic acid (ASA) for reducing PGE2 levels in these tissues, and to improve our understanding of potential tumor-derived stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…This concept was supported by data showing that samples from surrounding nontumoral mucosa produced more PGE 2 than samples from tumor. This is in agreement with data reported by Schuon et al ( 39 ), who found high levels of PGE 2 in the tumor-surrounding nonmalignant mucosa in patients with HNSCC. PGE 2 -dependent tumor angiogenesis has been attributed to COX-2 and mPGES-1 expression in tumors such as HNSCC (5,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 94%
“…This concept was supported by data showing that samples from surrounding nontumoral mucosa produced more PGE 2 than samples from tumor. This is in agreement with data reported by Schuon et al ( 39 ), who found high levels of PGE 2 in the tumor-surrounding nonmalignant mucosa in patients with HNSCC. PGE 2 -dependent tumor angiogenesis has been attributed to COX-2 and mPGES-1 expression in tumors such as HNSCC (5,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, HNSCC are able to secrete PGE2 16,18-19, but the contribution of PGE2 receptors to HNSCC progression is not fully established. In colon cancer, COX-2 overexpression and PGE2 production is often linked with EP2 activation, which triggers growth promoting signaling pathways such as β-catenin20 as well as leukocyte recruitment and angiogenesis21 by multiple G-protein regulated intracellular signaling pathways4, 21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of cycloxygenase‐2 (COX‐2) in the oral mucosa has been associated with increased risk of head and neck cancer 6, 9–13. Several processes linked to carcinogenesis can be influenced by the enhanced synthesis of prostaglandin E 2 (PGE 2 ) 14–17. Therefore, COX‐2 has been intensively studied for development of chemopreventive agents.…”
mentioning
confidence: 99%